The good, the bad, and the aggregate - Critchfield, Thomas S. (2000)
To evaluate progress and focus goals, scientific disciplines need to identify relations that are robust across many situations. One approach is the literature review, which characterizes generality across studies. Some writers (e.g., Baron & Derenne, 2000) claim that quantitative literature reviews, but not narrative reviews, violate the methodological precepts of behavior analysis by pooling data from nonidentical studies. We argue that it is impossible to assess generality without varying the context in which relationships are studied. Properly chosen data-aggregation strategies can reveal which behavior-environment relations are general and which are procedure dependent. Within behavior analysis, reluctance to conduct quantitative reviews may reflect unsupported assumptions about the consequences of aggregating data across studies. Whether specific data-aggregation techniques help or harm a research program is an empirical issue that cannot be resolved by unstructured discussion. Some examples of how aggregation has been used in identifying behavior-environment relations are examined.